Centrally administered state-owned enterprises' engagement in China's public–private partnerships: a social network analysis. Issue 3 (3rd July 2021) - Xiong, Min; Whetsell, Travis A.; Zhao, Jerry (Zhirong); Cheng, Shaoming
ABSTRACT: A salient characteristic of China's public–pgrivate partnerships (PPPs) is the deep involvement of state-owned enterprises (SOEs), particularly those administered by the central/national government (CSOEs). In this research social network analysis (SNA) was used to examine the role of different actors in transport and environmental protection PPPs in China in the period 2012–17. The results largely confirm the resource-based view and resource-dependency theory, showing that while CSOEs are dominant in both sectors, their dominance and control is greatest in transport sector projects that are more dependent on their accumulated experience, expertise, human capital assets and managemgent skills, that their dominance has increased over time, and that it is aligned with the provincial distribution of Chinese CSOEs.